Digital and Scientific Literacy with Games: A Pedagogical Process Based on System Engineering - Rodrigues, Ana Paula Cavadas; Fernandes, Raquel Moreira Machado; Teixeira, Leniah Lima; Alves, Gabrielle Bandeira; Oliveira, Carlo Emmanoel Tolla de; Motta, Claudia Lage Rebello da (Journal on Interactive Systems, 2021)
<span class="NormalTextRun SCXW76140887 BCX0" data-ccp-parastyle="AbstractBody" data-ccp-parastyle-defn=""ObjectId":"75b8654f-967a-4fcd-adaa-93b49b42cf5f|148","ClassId":1073872969,"Properties":[134233614,"true",134234082,"true",201340122,"2",201341983,"0",268442635,"18",335551500,"0",335551550,"6",335551620,"6",335559685,"40",335559731,"284",335559737,"0",335559739,"120",335559740,"240",335559991,"6",469769226,"Times New Roman",469775450,"AbstractBody",469777841,"Times New Roman",469777842,"Times New Roman",469777843,"Times New Roman",469777844,"Times New Roman",469778129,"AbstractBody",469778324,"No Spacing"]">This study presents a Brazilian teaching-learning experience in basic education where game development is used to promote both digital and scientific literacy throughout the National Common Curricular Base (BNCC). Focused on students’ cognitive aspects, the approach presents a pedagogical architecture based on systems development. Thus, it was possible to catalyze convergence between interest in the Science curricular program and the result of knowledge acquisition - such as skills development - by its means. The experiment was carried out centered on genetics studies where students collaboratively produced a digital game, improving in school assessment performance as an outcome. Therefore, we corroborate the effectiveness of creating games as an educational strategy able to optimize aspects of creativity, communication, collaboration, logical reasoning, problem-solving, abstract thinking and resilience.